Evaluación de dos dilutores comerciales (triladyl - andromed) en la viabilidad espermática del semen bovino refrigerado a diferentes horas post-colección - Jaramillo Jaramillo, Michelle Alejandra (2021)
Between the reproductive biotechnologies that allow enhance bovine production is the artificial insemination, a technique that present great advantages in the animal genetic progress. Between the limitations of this technique is the low percentage of sperm viability during procecution of chilled semen cryopreserved. The present work was realized in Nambacola parish, Gonzanamá canton, Loja province. The objetive of this research was to evaluate two commercial dilutors (Triladyl - AndroMed) in the spermatic viability of chilled bovine semen at 12, 24, 36 and 48 hours post-collection; 2 Brown Swiss and Holstein Friesian breed bulls were used, with ages between two and four years, with a good body condition (3.5), the same ones that were collected using the artificial vagina; 10 ejaculates were extracted for each specimen, obtaining a total of 20 samples. The semen was diluted in AndroMed and Triladyl, later it was packed and refrigerated in straws of 0.5ml at a temperature of 0.5°C until the moment of its evaluation. In the analysis postrefrigeration the Brown Swiss bovine breed got the best results to the valoration micro and macroscopic with a volume of 5.55ml, a spermatic concentration of 675 millions spz/ml, mass motility of 82.6%, individual motility of 74.6% and a vitality of 83%, while the Holstein bovine breed showed lower values with a volume of 3.7ml, a spermatic concentration of 500 millions spz/ml, mass motility of 76%, individual motility of 67.8% and a spermatic concentration of 75.8%, regarding the post-collection refrigeration time and dilutor used according the values obtained, statistically significant differences (P <0.05) were found at 12 hours with the Triladyl dilutor presenting better characteristics compared to the other treatments with 83.2%. The results were analyzed using an ANOVA analysis, to evaluate the effect of the different hours with respect to diluters and races. Keywords: AndroMed; Triladyl; refrigeration; Brown Swiss; Holstein Friesian